Unveiling the Potential of Big Data for Agricultural Research Libraries: Perspectives from Nigeria - Adewojo, Akinade Adebowale; Olubiyi, Timilehin Olasoji, PhD; Hamzat, Saheed Abiola PhD; Ayodeji Yusuf Ajani; Aderinola Ololade Dunmade PhD (Citakonsultindo, 2023)
This study examined the perception of use associated with big data in agricultural research institutes' libraries. A descriptive design was employed, and thematic analysis was done on the information obtained through key informant interviews. The population of this study consists of two librarians from each of the agricultural research institutes' libraries. In the study, four research questions were addressed. The results showed librarians believe big data assists them in providing clear and straightforward information that will quickly aid the demands of the researchers in the institutes. The study also revealed how big data helps librarians better understand how they can meet the information demands of researchers. The difficulties associated with the use of big data in agricultural research libraries in Kwara State, Nigeria, stem from the presence of incompetent personnel, insufficient funds, irregular electricity supply, sluggish internet connectivity, and the expense of training and retraining on big data. In conclusion, the perception of the use of big data in agricultural research libraries allows librarians to streamline operations and services to exactly what the researcher wants. Based on the findings, the study recommends ensuring the effectiveness of big data, agricultural research libraries should recruit more data analyst experts to manage big data in their libraries and ensure alternative power generation such as solar systems, inverters or standby generating machines are made available.